Phase field simulation of microstructure evolution and process optimization during homogenization of additively manufactured Inconel 718 alloy - Chen, Miaomiao; Du, Qiang; Shi, Renhai; Fu, Huadong; Liu, Zhuangzhuang; Xie, Jianxin (Frontiers in Materials, 2022)
An in-depth and integral understanding of the microstructural evolution during thermomechanical process (TMP) is of great significance to optimize the manufactural process for high-quality components via additive manufacturing. The solidified microstructure model of Inconel 718 alloy fabricated via laser powder bed fusion (LPBF) is established by multiphase field model firstly. Furthermore, the microstructural evolution during homogenization process is simulated and optimized in this study. Phase field simulation results show that the concentration gradient of Nb along the radius of the cellular substructure decreases from the initial 1.217 wt.% to 0.001 wt.%, and 67% area fraction of the Laves phase dissolves at the homogenization time of 0.5 h, which have achieved the homogenization purpose. The experimental results show that the average grain size decreases from 9.4 μm to 5.9 μm at the homogenization time from 1.5 h (the standard AMS 5383) to 0.5 h, which resulted in the increase of yield strength and tensile strength of the aged alloy by 14% and 6%, respectively. This research can provide guidance and reference for the microstructural control as well as the TMP parameters design of the additive manufactured alloys.